2005
DOI: 10.1152/ajpendo.00441.2003
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-CoA provision and the acetyl group deficit at the onset of contraction in ischemic canine skeletal muscle

Abstract: -We examined the effects of increasing acetylcarnitine and acetyl-CoA availability at rest, independent of pyruvate dehydrogenase complex (PDC) activation, on energy production and tension development during the rest-to-work transition in canine skeletal muscle. We aimed to elucidate whether the lag in PDC-derived acetyl-CoA delivery toward the TCA cycle at the onset of exercise can be overcome by increasing acetyl group availability independently of PDC activation or is intimately dependent on PDCderived acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…The tissue concentrations used in the present study (0.12-1.00 mM) were approximately an order of magnitude lower than those used to maximally acetylate free carnitine and CoA in canine skeletal muscle [15] and human skeletal muscle at rest [42][43][44]. This indicates that the observed acetylcarnitine formation was not hindered Acetate Acetylcarnitine Model Fit Fig.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The tissue concentrations used in the present study (0.12-1.00 mM) were approximately an order of magnitude lower than those used to maximally acetylate free carnitine and CoA in canine skeletal muscle [15] and human skeletal muscle at rest [42][43][44]. This indicates that the observed acetylcarnitine formation was not hindered Acetate Acetylcarnitine Model Fit Fig.…”
mentioning
confidence: 68%
“…In rat skeletal muscle, 98% to 99% of extra acetylCoA produced is buffered by acetylcarnitine [14]. Since the mitochondrial inner membrane is impermeable to acetylCoA, CAT is essential in the metabolism of acetate, as was shown in canine skeletal muscle [15]. After transformation to acetylcarnitine it traverses the inner mitochondrial membrane via acetylcarnitine translocase (ATL) where a mitochondrial CAT transfers the acetyl group back to CoASH upon which acetylCoA can enter the TCA cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kindig et al (31) reported much faster J o kinetics in isolated myocytes in the presence of a CK inhibitor. It is important to note, however, that elevating cellular TCr, via dietary Cr supplementation, failed to slow J o kinetics in exercising human muscle (29), as the Meyer model would predict.A different conceptual approach to what accounts for the sluggish cellular adjustment to ATP demand describes the response as "metabolic inertia" (18,22,26,50). In this view, a lag in the availability of oxidative substrate accounts for the delay in the matching of oxidative phosphorylation to ATP demand (22,26,50,55).…”
mentioning
confidence: 99%
“…The studies by Bangsbo et al (Bangsbo et al 2002), Rossiter et al (Rossiter et al 2003) and Jones et al (Jones et al 2004) failed to make concurrent measurement of both acetyl group availability and pyruvate dehydrogenase complex activation status before and during exercise. Accurate measures of both of these factors are necessary when evaluating the acetyl group deficit (Roberts et al 2002;Roberts, Loxham, Poucher, Constantin-Teodosiu, & Greenhaff, 2005). In addition, Savasi et al (Savasi et al 2002) and Jones et al (Jones et al 2004) utilised intermittent exercise protocols, which are likely to blunt the effects of dichloroacetate infusion, since prior exercise causes activation of the pyruvate dehydrogenase complex.…”
Section: Introductionmentioning
confidence: 99%